Auditory interference and phonological encoding in reading for meaning - Christowitz, Joan (My University, 2014)
The main aim of the present research was zo investigate the effects of auditory interfering stimuli and an articulatory suppression task on pre- and postlexical phonological encoding during reading. Sixty undergraduate students performed a Prose Comprehension task (Experiment 1) and a Nonword-rhyming task (Experiment 2) under conditions of INTERFERENCE and NO INPUT. An analysis of covariance and post-hoc t-tests revealed that semanticslly and syntactically complex verbal auditory input had the greatest interfering effect on the speed of performance of the Prose Comprehension task, No other results were statistically significant, Twenty undergx-aduate students (Experiment 3) and twenty children (ten dyslexics, ten normal readers - Experiment 4) performed a Magnitude Judgment task under conditions of INTERFERENCE and NO INPUT. Prose auditory interference and an articulatory suppression task did not significantly slow down the performance of skilled readers while prose input did slow down the performance of both dyslexic and normal children. Magnitude Judgment accuracy data was not analysed due to the low error rate. The results of. the present research ware interpreted within the framework of a neuro-cognitive model of reading based largely on Luria's neuropsychological model of the "working brain" and Morton's "Logogen" model of word recognition.
A thesis Submitted to the Faculty of Arts, University of the, Witwatersrand, Johannesburg,, in fulfilment of the requirements for the degree of Master of Arts. Johannesburg 1983